Modification of nanosilica by low volatile silanes in pseudo-liquid state - Telegeev, I. G.; Pakhlov, E. M.; Voronin, E. F. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2008)
The interaction of nanosized silica and low volatile alkyl- and alkylacrylate-containing di- and trialkoxysilanes at atmospheric pressure in pseudo-liquid state using a reactor of intensive mixing has been studied by means of IR-spectroscopy. Optimum conditions of interaction were defined. The ratio of parent free silanol and grafted organosilyl groups was found to be 1.4:1. This means that about 55 % of silane molecules react with surface silanol groups in monofunctional and 45 % – in bifunctional way.